Functional Parallelism of Detailed and Rough Speech Processing at the End of Infancy. - Teickner, Claudia; Becker, Angelika B. C.; Schild, Ulrike; Friedrich, Claudia K. (Infancy)
Although realization of the same speech sound is far from being consistent across different contexts, speech recognition has to rely on phonetic detail in order to detect words. So far, it appeared that young infants cannot avoid noticing subtle speech sound variation whenever it occurs. Only later on, they are able to tolerate speech sound variation in some word recognition tasks. Here, we test whether this ability is associated with the time infants start storing their first word forms. We recorded event‐related potentials (ERPs) in a priming paradigm. German words (targets) followed syllables (primes) with a different amount of phoneme overlap. We tested infants at three, six, and nine months after birth. ERPs reflected sensitivity to prime‐target variation in a single phoneme in three‐month‐olds, tolerance to this in six‐month‐olds, and both processing aspects in nine‐month‐olds. Our findings reveal individual developmental priorities for different aspects of speech processing, with very detailed speech processing dominating at around 3 months, rough processing dominating at around half a year after birth, and an architecture of parallel rough and detailed processing at around 9 months. Functional parallelism at the end of infancy might explain the heterogeneous pattern of results regarding the degree of acoustic detail that toddlers appear to consider at different ages and across different paradigms.